2-[(1E)-({[(Benzylsulfanyl)methanethioyl]amino}- imino)methyl]-6-methoxyphenol: crystal structure and Hirshfeld surface analysis - Md Yusof, Enis Nadia; Jotani, Mukesh M.; Tiekink, Edward R. T.; Ravoof, Thahira B. S. A. (International Union of Crystallography, 2016)
The title dithiocarbazate ester, C16H16N2O2S2, comprises two almost planar residues, i.e. the phenyl ring and the remaining 14 non-H atoms (r.m.s. deviation = 0.0410 Å). These are orientated perpendicularly, forming a dihedral angle of 82.72 (5)°. An intramolecular hydroxy-O—H⋯N(imine) hydrogen bond, leading to an S(6) loop, is noted. An analysis of the geometric parameters is consistent with the molecule existing as the thione tautomer, and the conformation about the C=N bond is E. The thione S and imine H atoms lie to the same side of the molecule, facilitating the formation of intermolecular N—H⋯S hydrogen bonds leading to eight-membered {⋯HNCS}2 synthons in the crystal. These aggregates are connected by phenyl-C—H⋯O(hydroxy) interactions into a supramolecular layer in the bc plane; these stack with no directional interactions between them. An analysis of the Hirshfeld surface confirms the nature of the intermolecular interactions.